2021
DOI: 10.31219/osf.io/dh3y2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Anotasi Bibliografi_Muhammad Ridwan

Abstract: Anotasi Bibliografi_Muhammad Ridwan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
1
10

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 0 publications
0
13
1
10
Order By: Relevance
“…8 The high incidence of fractures in men is due to the high mobility and activity in men, especially when driving, thereby increasing the risk of injury to men. 6 However, the results of the sex distribution in this study were different from several other studies which found that the female sex was the most experienced fracture. As the study conducted by Chitnis et al found that the percentage of fractures in the long bones was found to be higher in women, namely 50.8% and 55.3% for the incidence of fractures in the femur and humerus, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…8 The high incidence of fractures in men is due to the high mobility and activity in men, especially when driving, thereby increasing the risk of injury to men. 6 However, the results of the sex distribution in this study were different from several other studies which found that the female sex was the most experienced fracture. As the study conducted by Chitnis et al found that the percentage of fractures in the long bones was found to be higher in women, namely 50.8% and 55.3% for the incidence of fractures in the femur and humerus, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…Penelitian Tindakan Kelas merupakan suatu pencermatan terhadap kegiatan belajar yang berbentuk sebuah tindakan, yang sengaja dimunculkan dan terjadi dalam sebuah kelas secara bersama. [11] Prosedur kerja dalam penelitian tindakan kelas terdiri atas empat komponen, yaitu perencanaan (planning), tindakan (acting), pengamatan (observing), dan refleksi (reflecting), yang keempatnya merupakan satu siklus. [ Instrumen yang digunakan untuk pengumpulan data pada penelitian ini adalah instrumen penilaian hasil belajar siswa berupa rubrik penilaian kinerja.…”
Section: Project Based Learning/pembelajaran Berbasisunclassified
“…Right with the goals and objectives c. Impact on poverty reduction and job creation. 48 While the distribution is indirectly an empowerment and coaching program with partners that have institutional and professional eligibility criteria. This can be through zakat management institutions, baitul mal wa tamwil, empowerment institutions, foundations, or social organizations on a national or international scale in accordance with The Waqf assets that have been handed over to the professional nazir are then managed more productively through management or utilization that can increase the productivity of the Waqf land.…”
Section: Nazir Conceptmentioning
confidence: 99%